Development and validation of stability-indicating UHPLC-UV-MS tandem methods for lenalidomide assay, related substances, and genotoxic impurity monitoring - Agtas, Cagan; Atici, Esen Bellur (Elsevier, 2025)
Lenalidomide, a potent immunomodulatory drug, is widely used in the treatment of myelodysplastic syndrome. To investigate its degradation behavior under stress and stability testing conditions, we developed and validated a novel stability-indicating ultra-performance liquid chromatography (UHPLC)-UV-MS tandem method with high specificity, precision, accuracy, and robustness. An Acquity UPLC Phenyl column (100 x 2.1 mm, 1.7 mu m) was used for impurity profiling and quantification of lenalidomide at a detection wavelength of 254 nm, with an injection volume of 1.0 mu L and controlled sample and column temperatures of 15 degrees C and 30 degrees C, respectively. The diluent consisted of 0.1 % formic acid and acetonitrile (90:10, v/v), while the mobile phases were 0.1 % formic acid (Mobile Phase A) and acetonitrile (Mobile Phase B). A 20-minute gradient elution at a flow rate of 0.2 mL/ min was used for impurity analysis, whereas a 7-minute gradient at 0.3 mL/min was applied for assay determination. The method demonstrated good linearity for all analytes, ensuring reliable quantification. Stress and photostability studies revealed that lenalidomide was stable under high temperatures (105 degrees C for 10 days) and daylight/UV exposure but exhibited significant degradation under hydrolytic and oxidative conditions. Hydrolysis led to the formation of major degradation products A, B, and E, whereas oxidative stress conditions generated impurities C (-NH2-* -NO2) and I (-NH2-* -NH-OH). Methanol, commonly used in lenalidomide synthesis and analytical methods, was found to play a critical role in impurity formation. Methanolysis products J and K were identified as constitutional isomers arising from the ring-opening of the glutarimide moiety, which was confirmed by UHPLC-Q-TOF-MS and NMR analyses. The UHPLC-UV-MS method also reliably monitored the potentially genotoxic impurity G, classified as a Class 2 impurity according to ICH M7 guidelines, ensuring its levels remained below the Toxicological Threshold Concern (TTC, 1.5 mu g/day, 60 ppm) for patient safety as per health authority requirements. This comprehensive analytical approach not only ensures the stability and safety of lenalidomide but also provides critical insights into its degradation pathways. The findings contribute to improved impurity control strategies, manufacturing process optimization, and regulatory compliance, benefiting the broader class of glutarimide-containing drug substances such as pomalidomide and thalidomide.
Keywords: Lenalidomide; Stability; Degradation; UHPLC-UV-MS; Validation; Stress testing